2015
DOI: 10.1007/s11356-015-4246-8
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged starvation and subsequent recovery of nitrification process in a simulated photovoltaic aeration SBR

Abstract: The ability of a new SBR (sequencing batch reactor) based on simulating photovoltaic aeration for maintaining nitrification activity under a 25-day starvation period was studied. The activity and abundance of ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB) and the diversity of AOB were investigated. The measured biomass decay rates were 0.017 day(-1) and 0.029 day(-1) for AOB and NOB, respectively. These decay rates correlated well with AOB and NOB population quantified by real-time PCR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…After organic matter started being fed and cycle configuration was changed (days 147-171), the abundance of AOB and their population diversity were drastically reduced, with Cluster 6a members becoming steadily prevalent throughout the rest of Stages II and III. In this sense, Ma, et al [32] reported that Cluster 6a phylotypes dominated the nitrifying biomass of an SBR treating semi-synthetic wastewater bearing similar ranges of concentration of organic matter and ammonia; in addition, these authors found that Cluster 6a-related populations survived well to anoxic starvation and were able to fast recover the ammonia oxidation activity after resuming operation, in line with the observations presented here. Relative abundances of the OTU0157 and OTU0324 abruptly decreased from day 147 onwards, after the cycle configuration was modified.…”
Section: Diversity Of Bacteria In the Sbr Identified By Illumina Sequ...supporting
confidence: 88%
See 1 more Smart Citation
“…After organic matter started being fed and cycle configuration was changed (days 147-171), the abundance of AOB and their population diversity were drastically reduced, with Cluster 6a members becoming steadily prevalent throughout the rest of Stages II and III. In this sense, Ma, et al [32] reported that Cluster 6a phylotypes dominated the nitrifying biomass of an SBR treating semi-synthetic wastewater bearing similar ranges of concentration of organic matter and ammonia; in addition, these authors found that Cluster 6a-related populations survived well to anoxic starvation and were able to fast recover the ammonia oxidation activity after resuming operation, in line with the observations presented here. Relative abundances of the OTU0157 and OTU0324 abruptly decreased from day 147 onwards, after the cycle configuration was modified.…”
Section: Diversity Of Bacteria In the Sbr Identified By Illumina Sequ...supporting
confidence: 88%
“…In contrast with the results observed for total Bacteria and AOB, the quantifications of NOB in the two samples of Stage III rendered values close to the limit of detection of the qPCR method. Several studies have previously reported that NOB are more sensitive than AOB to starvation and take longer to recover their metabolic activity after addition of substrates [31,32]. The difference of the activity recovery rates among AOB and NOB has been related with a delayed transcriptional response of the nxrB genes to the addition of substrates, which require longer periods than the amoA genes, leading to the subsequent dominance of AOB over NOB populations [33].…”
Section: Quantification Of Microbial Groups By Quantitative Pcr (Qpcr...mentioning
confidence: 99%
“…Additionally, the drop in activity of AOB and NOB was also possibly caused by cell decay that had been evidenced by the rise of ammonium and phosphate concentration in the medium (Supplementary Materials Figure S1). Ma et al [8] also observed deterioration of activity of nitrifiers with a specific decay rate at 0.017 d −1 for AOB and 0.029 d −1 for NOB under anoxic-anaerobic starvation conditions over 25 days. Other data relating to the changes in other parameters, including COD, NH 4 + _N, NO 2 − _N, NO 3 − _N, PO 4 3− _P, MLSS, and MLVSS during the starvation period, can be found in the Supplementary Materials Figures S1 and S2.…”
Section: Anaerobic Starvationmentioning
confidence: 90%
“…Similarly, several incidents could lead to long-term starvation of the activated process, such as power loss due to natural disasters, lockdown due to a severe pandemic, long-term holidays, etc. Some negative impacts including a loss in AOB and NOB activities [8,9], loss of biomass, and the appearance of opportunistic microorganisms [10] have been reported for systems subjected to starvation. As the nitrifiers are autotrophs and require a longer growth time than heterotrophs responsible for COD removal or denitrification, those hazardous events may have more pronounced effects on the nitrification process.…”
Section: Introductionmentioning
confidence: 99%